2015
DOI: 10.1111/sltb.12154
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth Monitoring of Patients with Schizophrenia and Suicidal Ideation

Abstract: A telehealth system was developed to monitor risk following hospitalization for suicidal ideation. We hypothesized that 3 months of telehealth monitoring will result in a greater reduction in suicidal ideation. Veterans with schizophrenia admitted with recent suicidal ideation and/or a suicidal attempt were recruited into a discharge program of VA Usual Care with daily Health Buddy© monitoring (HB) or Usual Care (UC) alone. Fifteen of 25 were randomized to HB and 10 received UC. Daily adherence in the use of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 34 publications
1
11
0
1
Order By: Relevance
“…The overall adherence for the remaining 20 participants for logging in daily to the telehealth system exceeded 80% for each of the 3 months while they were in the study. This is consistent with what was reported previously for the same population of Veterans (Kasckow et al 2015). …”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The overall adherence for the remaining 20 participants for logging in daily to the telehealth system exceeded 80% for each of the 3 months while they were in the study. This is consistent with what was reported previously for the same population of Veterans (Kasckow et al 2015). …”
Section: Discussionsupporting
confidence: 94%
“…The current study also assessed acceptability; acceptability has not been reported previously in studies involving suicide monitoring with this population (Kasckow et al 2015). Negative statements indicated that patients at times became frustrated when communicating with a machine rather than with a human.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Patients may also be alerted, for example, with automatically generated e-mail or text messages that could also function as reminders of safety plans (Stanley and Brown, 2012). Accordingly, first tele-health projects have been implemented with promising results (Kasckow et al, 2015). This calls for a cooperative multi-center study in the development of early suicide warning systems.…”
Section: Discussionmentioning
confidence: 99%
“…25 Literatürde tele psikiyatri uygulamalarının; dikkat eksikliği ve hiperaktivite bozukluğunda, depresyonda, demansta, şizofrenide, intiharı önlemede, travma sonrası stres bozukluğunda, panik bozuklukta, madde bağımlılığında, yeme bozukluklarında ve sigara içmeyi önlemede etkili olduğunu gösteren çalışmalar bulunmaktadır. 11,[37][38][39][40][41] Bu etkinliğin yanı sıra tele psikiyatrinin kullanılamadığı bir tanı grubu ya da demografik özellik belirtilmemektedir. 27 Ancak, fiziksel ya da bilişsel engeli sebebiyle teknolojik ekipmanı kullanamayacak durumda olan bireyler için uygun bir tercih olmadığı belirtilmektedir.…”
Section: Psi̇ki̇yatri̇de Tele Hemşi̇reli̇kunclassified